Simulazione dell'Assegno Unico Universale: I benefici della misura e gli effetti redistributivi - Marco Biagetti; Valentina Ferri; Francesco Figari; Salvatore Marsiglia (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2022)
This paper aims at analyzing the new "Assegno Unico Universale" (Single All-Purpose Allowance) introduced in Italy since February 2022 and its ability to reach the objectives that policymakers intend to achieve. This task is carried out by means of EUROMOD, a tax-benefit microsimulation model that considers pensions, means and non-means tested benefits. The allowance aims to beef up policies aimed at supporting households with children, in order to bring them to levels of wellbeing similar to other European countries. The new measure replaced previous policies and endeavors to benefit otherwise excluded people (i.e. those families whose income is so low that they did not pay any income tax or – oppositely – considerably wealthy households). What is more, an effort was made to even out treatment of employees and self-employed workers. In particular, the latter were virtually excluded by previous policy measures. New available data show that the take-up rate of this new measure has taken a while to reach 95% of the eligible households in late June 2022. This time lag has been probably determined by scanty information, insecurity and the predictable slowness of the "Red Tape" - all problems that now seem to have been overcome. The EUROMOD simulations presented here show a certain increase in public deficit obviously due to the hike in transfers, which unarguably benefit a higher number of households compared to previously available measures. Unsurprisingly, the number of households paying the income tax is also shown to increase: this is due to the abolition of tax deductions for dependent children up to twenty-one years of age. This increase concerns households in the lower deciles of the so called "ISEE" income. Those lower deciles disproportionately include families that did not pay income taxes under the old policies. Our results also show a reduction in inequality coupled with a slight improvement in income redistribution as well as an increase in the social welfare index. The progressivity of the system however is projected to go down. This may seem counterintuitive but it is quite natural instead: in fact, beneficiary households can also be rather affluent. After all, the new tool seems well conceived as it is able to increase social welfare, helping without rising inequality although reducing tax progressivity to a very small extent. The same applies to poverty risk based on disposable income: the number of households and the magnitude of this risk is projected to decrease more the lower the disposable income compared to the median. Furthermore, this risk is shown to be consistently smaller for households composed by an adult and one or two children, while it slightly rises as the number of underage children gets higher. This fact hints at designing completely different tools to tackle the low natality trap Italy is entangled in. Additionally, there are still doubts on the possibility of an effective income redistribution towards females who are not primary, classical breadwinners in the Italian social model. Indeed, it can be argues that the new transfer could favor the creation of shadow labor markets and lower the official female participation rate. Other potential weaknesses concern dependent children over 21 years of age for whom households previously obtained a financial contribution which has been canceled; new allowances for children born from unmarried parents; the treatment of particular incomes (i.e. those derived by owing a house, other real estates or even non-liquid financial assets) which have a low liquidity compared to purely monetary revenues. On a closer inspection, the latter is a vulnerability of the ISEE income tax return, which should be faced by Italian policymakers in the near future at a time when inflation hikes are rapidly eroding purchasing power of households worldwide.
Keywords: 330; Welfare Benefits; Taxation; Poverty; Microsimulation; Households